'Sociali persona ludens': the social component of human play. Issue 4 (2nd October 2022) - Lebed, Felix
ABSTRACT: Social background is a vital element of human play, realizing with the overt and covert transference of social norms as relevant values in public discourse. The interdisciplinary discussion proposed in this article makes it possible to propose a 3D model of 'sociali persona ludum' in the concluding part of the study. The model suggests three kinds of domains that together, create each socially dependent person's play: (1) the emergent domain of escapes to the so-called 'being there' of play (2) the domain of contents, and (3) the domain of uncertainties. They are functions of different basic features of human play that are analyzed here – the quantity and quality of playing agents, plots of games, and interactions between agents – placed on three Cartesian axes. In addition to the scholarly thesis suggested by this model, one can see it as a possible framework for for different applicative needs.